Juridical Analysis of the Crime of Beating Resulting in Death by a Minor Perpetrator: Study of Decision No.1/ Pid.Sus-Anak/2024/PN Mme - Felisitha, Gabriela L; Aven, Ghina Shalsabila (IHSA Institute, 2025)
Children, as individuals in their developmental stages, have the right to legal protection, including when facing the criminal justice system. However, the involvement of children as perpetrators of criminal acts raises specific issues, as seen in Decision No. 1/Pid.Sus-Anak/2024/PN Mme related to a case of assault that resulted in death. This research focuses on the judge's considerations in imposing sentences and the extent to which the principle of restorative justice is applied in accordance with the Child Criminal Justice System Law. In this study, the method used is normative legal research with a statutory approach, and conceptual approach. This study analyzes Decision No. 1/Pid.Sus-Anak/2024/PN Mme by examining relevant positive norms and data obtained through library research, which is analyzed qualitatively. The research results show that the judge placed more emphasis on proving the elements of the crime according to Article 170 paragraph (2) sub-paragraph 3 of the Criminal Code without optimizing the restorative justice approach. Although age and reconciliation factors are considered, the diversion process is not implemented thoroughly, resulting in juvenile sentencing not reflecting the restorative principles mandated by the SPPA Law. Law enforcement needs to strengthen the rehabilitative approach by optimally utilizing litmas and psychosocial analysis, as well as prioritizing non-custodial sanctions. The implementation of restorative justice must be internalized through diversion and penal mediation with the support of cross-institutional collaboration and adequate legal infrastructure